2003
DOI: 10.1016/s0010-9452(08)70880-3
|View full text |Cite
|
Sign up to set email alerts
|

On the Involvement of Prefrontal Networks in Cognitive Ageing

Abstract: Normal ageing is associated with a wide variety of disturbances in the structure and function of the human brain. Recent neuroimaging studies suggest that the prefrontal cortex (PFC) is particularly vulnerable to the effects of ageing. These findings are compatible with the so-called 'frontal ageing hypothesis' which has been formulated on the basis of neuropsychological research on non-pathological ageing. We will argue on the basis of recent structural and functional neuroimaging studies that this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
135
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(161 citation statements)
references
References 174 publications
19
135
1
3
Order By: Relevance
“…Moreover, their interaction is involved in neuronal plasticity mechanism and neuronal disorders such as autism (Südhof 2008). It has also been reported that the synaptic plasticity reduces during aging (Burke and Barnes ) and impairs executive functions such as working memory and attention (Tisserand and Jolles 2003). Therefore, it is likely that Nrxn1 and Nlgn3 are involved in age-related decline in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their interaction is involved in neuronal plasticity mechanism and neuronal disorders such as autism (Südhof 2008). It has also been reported that the synaptic plasticity reduces during aging (Burke and Barnes ) and impairs executive functions such as working memory and attention (Tisserand and Jolles 2003). Therefore, it is likely that Nrxn1 and Nlgn3 are involved in age-related decline in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The deficits in alcoholic patients can be interpreted in the context of the frontal lobe hypothesis, which asserts a specific vulnerability of the prefrontal cortex to the neurotoxic effects of alcohol (Parsons, 1994). In addition, the frontal lobes have been reported to be disproportionately affected by normal aging (Tisserand & Jolles, 2003;West & Covell, 2001). The similarities across the three investigations thus suggest that humor processing and mentalizing deficits can occur across different etiologies involving dysfunction of the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 94%
“…The current study set out to explore five key potential mediators of age-related decline in the ability to decode emotional prosody: 8 Decoding emotional prosody… Frontal Lobe Load: One theory of cognitive aging supposes much age-related cognitive decline can be explained by frontal lobe deterioration (West, 1996), particularly prefrontal cortex (Tisserand & Jolles, 2003). Performance on a 'frontal lobe' task would therefore be more likely to decline with age than a task whose performance was less dependent on the frontal lobe.…”
Section: Potential Mediatorsmentioning
confidence: 99%